Violación del principio constitucional de legalidad penal en el delito de feminicidio en el Perú 2020 - Álava Guevara, Víctor Rafael (2022)
The crime of Femicide, which is in force, presents two indeterminate legal formulas, which are "the one" and "because of his condition as such". These endings differ in the wording and interpretation that the doctrine gives to them, generating confusion among authors and legal operators. The objective of the thesis is to explain the legal foundations that support the violation of the Constitutional Principle of Criminal Legality in the crime of Femicide of the Peruvian Penal Code, 2020. To achieve this end, the dogmatic method was used, which considers as an object of knowledge the legal system of a country. In turn, the researchers collected the Feminicide wordings of the most important legislations in Latin America; also the position of the doctrine against the incorporation and configuration of Femicide and; the opinions of professionals with recognized experience in the field of Criminal Law in the city of Iquitos, Peru. Consequently, it has been possible to determine that the criminal type of Femicide in Peru violates the Principle of Criminal Legality by not meeting all the validity requirements that a norm must have, more precisely, it does not meet the requirement of a certain Law, since, the clauses "the one" and "because of his condition as such" are indeterminate terms. Therefore, it is necessary for the legislator to modify the crime of Femicide in light of the Constitutional Principle of Criminal Legality, which demands the existence of certain norms in its formulation.